Topological identification of optical systems - Курской, Ю.С. (Radiotekhnika, 2019)
The purpose of this work is to create a topological model for the search and identification of hidden optical surveillance systems. The model is based on fractal ideas about the structure of the optical signal and the determination of the fractal dimension of the intensity distribution in the section plane of a laser pulse reflected from the target. It is shown that the approximation of the value of the fractal dimension to unity is a prerequisite for the classification of a target as an optical observation device. To classify the type of optical device, along with the fractal dimension, an ensemble of fractal features should be developed: the type of fractal signatures, the type of spatial spectrum and the values of spatial frequencies characterizing the signal structure.